Optimizing Combined Heat and Power Economic Dispatch Using a Differential Evolution Algorithm - Mahender, K.; Rao, Gundala Srinivasa; Kamalakar, Gangula; Venkateshwarlu, S.; Polasa, Swathi; Pulluri, Harish (E3S web of conferences, 2025)
The electrical load dispatch (ELD) optimizes the scheduling of various power plants to deliver the necessary power at the lowest operational cost. Implementing combined heat and power (CHP) units in contemporary power systems enhances energy efficiency and generates less environmental pollution compared to conventional units by producing electricity and heat at the same time. As a result, the ELD issue, including CHP units, transforms into a non-linear and non-convex challenge called CHP economic dispatch (CHPED), which aims to meet electrical and thermal demands at the lowest operational cost. The CHPED issue is examined by applying the Differential evolution (DE) approach. The algorithm's efficacy on 24-unit, 48-unit, and 96-unit systems is detailed. The results acquired are compared with other algorithms to evaluate the effectiveness of the DE algorithm. The findings proved the efficacy of the DE algorithms compared to other evolutionary algorithms.